Characteristics and Market Opportunities of Block Ice Factories at Batulicin Fishing Port Tanah Bumbu District - Rana Khairiyah Nasution; Emmy Lilimantik; Irma Febrianty (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Batulicin Fishing Port is a center of capture fisheries activities supported by the presence of block ice factories as an essential component of the cold chain system. This study aimed to analyze the characteristics of block ice factories in the Batulicin Fishing Port area and to assess the market opportunities for block ice at the port. The analytical method used was descriptive analysis. The results show that the block ice factories at Batulicin Fishing Port share similar characteristics in terms of machine-based production processes, dependence on water and electricity supplies, and direct marketing systems without intermediaries and with limited market coverage. The analysis of block ice demand indicates that total demand reached 476,325 kg/month, while total supply amounted to 472,300 kg/month. This gap indicates a positive market opportunity of 4,025 kg/month, suggesting that the availability of block ice at Batulicin Fishing Port is still insufficient to meet the needs of port service users.